Utilization of Agro-industrial Wastes for the Simultaneous Production of Amylase and Xylanase by Thermophilic Actinomycetes - Singh,Renu (2012)
Agro-industrial wastes such as sugarcane bagasse, wheat bran, rice bran, corn cob and wheat straw are cheapest and abundantly available natural carbon sources. The present study was aimed to production of amylase and xylanase simultaneously using agro-industrial waste as the sole carbon source. Seven thermophilic strains of actinomycete were isolated from the mushroom compost. Among of these, strain designated MSC702 having high potential to utilize agro-industrial wastes for the production of amylase and xylanase. Strain MSC702 was identified as novel species of Streptomyces through morphological characterization and 16S rRNA gene sequence. Enzyme production was determined using 1% (w/v) of various agro-industrial waste in production medium containing (g/100mL): K2HPO4(0.1), (NH4)2SO4(0.1), NaCl (0.1), MgSO4(0.1) at pH 7.0 after incubation of 48 h at 50°C. The amylase activity (373.89 IU/mL) and xylanase activity (30.15 IU/mL) was maximum in rice bran. The decreasing order of amylase and xylanase activity in different type of agro-industrial wastes were found rice bran (RB) > corn cob (CC) > wheat bran (WB) > wheat straw (WS) > sugarcane bagasse (SB) and rice bran (RB) > wheat bran (WB) > wheat straw (WS) > sugarcane bagasse (SB) > corn cob (CC), respectively. Mixed effect of different agro-industrial wastes was examined in different ratios. Enzyme yield of amylase and xylanase was ~1.3 and ~2.0 fold higher with RB: WB in 1:2 ratio.